Marked for life : one man's fight for justice from the inside - Wright, Isaac, Jr., 1962-; Sternfeld, Jon (St. Martin's Press, 2022)
"Marked for Life is the incredible memoir of a wrongfully imprisoned man's epic journey to free himself and others like him. Isaac Wright Jr. was wrongly accused of drug charges in New Jersey and sentenced to life in prison in 1991. He was arrested, tried, and convicted under a draconian "kingpin" statute even though he never dealt drugs a day in his life. Even though the prosecutor knew he was innocent, as did the detectives who investigated and arrested him. Even though the judge subverted legal procedure and coerced jurors. Even though his co-defendants-some of whom were guilty of the very things pinned on Isaac-were given freedom in exchange for their lies about what he did and who he was. He used the prison library to educate himself in the law and helped overturn the wrongful convictions of dozens of his fellow inmates before representing himself, proving his own innocence, and bringing down the powerful and corrupt men that had aligned against him"--